Comprendre la gestion des risques hydrométéorologiques au Cambodge - Tony Rey; Stéphanie Defossez (Territoire en Mouvement)
This article aims to show, through the example of Cambodia, how territorial framework is significant for public policies and risk management strategies. Bibliographic research and field observations directed the study case and explore risk management in a developing country which experienced recent political and military history with large consequences in the different institutions and for citizens. This evaluation shows several elements, the difficulties related to low development indicators, a military and political context still weak, difficulties in accessing data, the lack of knowledge about historical events and governance issues. It is also about the standardized approach sometimes not transferable to these territories with specifics characteristics.